Previous blood pressure measurement and associated factors in student adolescents - Magalhães,Marina Gabriella Pereira de Andrada (2015)
Objective To identify prevalence of previous blood pressure measurement and analyze some associated factors in adolescents.Methods This cross-sectional study included 6,077 adolescents aged 14 to 19 years. Demographic characteristics included (sex, age, period of study, region of residence, work, skin color, and economic) status, history of blood pressure measurement within last 12 months, local of blood pressure measurement, and reading obtained. To assess associations between previous blood pressure measurement with demographic characteristics and high blood pressure we used descriptive statistics and logistic regression analysis.Results Out of the adolescents, 56.8% reported no blood pressure measurement within the last 12 months. The health centers and the physician’s office were most mentioned places for blood pressure measurement (28.3% and 36.9%, respectively). Boys (odds ratio of 1.64 95%CI: 1.46-1.84) aged 14 to 16 years (odds ratio of 1.12; 95%CI: 1.01-1.25), whose economic status was unfavorable (odds ratio of 1.48; 95%CI: 1.32-1.67) were significantly associated with no blood pressure measurement. Working was a protective factor for was not blood pressure measurement (odds ratio of 0.84; 95%CI: 0.73-0.97).Conclusion Most of adolescents did not have their blood pressure measured within the last 12 months. Boys aged 14 to 16 years and those with unfavorable economic status had higher chance of not having their blood pressure measured.